PENGARUH JENIS MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MELON HIDROPONIK IRIGASI TETES DI DESA JLEGIWINANGUN, KECAMATAN KUTOWINANGUN, KABUPATEN KEBUMEN - Arifah Ani Roana; Umi Barokah (Nusantara Hasana Journal, 2025)
Hydroponic melon cultivation using a drip irrigation system is an alternative to increasing melon production amid the challenges of decreasing fertile agricultural land and increasingly unpredictable climate conditions. However, many farmers are still uncertain about selecting the most suitable growing medium for hydroponic melon cultivation. This study aimed to determine the best growing medium for hydroponic melon cultivation using a drip irrigation system in Jlegiwinangun Village, Kutowinangun District, Kebumen Regency. The research employed a Completely Randomized Design (CRD) non-factorial with four treatments and six replications, resulting in 24 experimental plots. Each plot contained three sample plants and two backup plants, totaling 120 melon plants. The growing media treatments consisted of M0: peat moss and manure, M1: rice husk charcoal, M2: cocopeat, and M3: a combination of rice husk charcoal and cocopeat. The results showed that the type of growing medium significantly affected the growth and yield of melon plants. The best performance was observed in the M3 treatment (rice husk charcoal + cocopeat), with the highest average plant height (30.8 cm), earliest flowering (20,67 days after transplanting), longest root length (46.33 cm), highest fruit weight (1.78 kg), largest fruit diameter (46.67 cm), longest fruit length (23.83 cm), and highest sweetness level (14.68° Brix).